CONSTRUCTION METHOD OF WAVELET BASE BASED ON GAUSSIAN FUNCTION AND ITS APPLICATION IN FAULT DIAGNOSIS OF ROLLING BEARING - WANG Peng; CHENG XiuFang (Jixie qiangdu)
In order to accurately diagnose the fault of rolling bearing,a wavelet base construction method based on Gaussian function is proposed. In this method,the superimposed Gaussian function is used as the initial model to construct the wavelet basis function. The coefficients of the wavelet basis function are determined by fitting the initial model with the vibration signal of rolling bearing. Through the analysis of fault signals of outer ring,inner ring and rolling element of 6205 rolling bearing,the results show that the new wavelet basis can effectively suppress the noise component in the signal,extract fault features,and realize accurate fault diagnosis of rolling bearing. Under the same decomposition conditions,the new wavelet basis can diagnose the running state of rolling bearing more accurately than Gaussian wavelet,so it has higher application value.